A New Olympic Ring Shaped Antenna for UWB Applications - Saidaiah, B.; Sudhakar, A.; Padma Raju, K. (Engineering, Technology & Applied Science Research, 2016)
In this paper, we propose a new Olympic Ring Shaped antenna for UWB applications. The proposed antenna is designed to operate from 3.1 to 10.6 GHz. It consists of a five circular ring shapes form an Olympic ring shape with a partial ground plane. A detail of proposed antenna simulation is done using CST software and measured results are presented and discussed.